Using T-SQL functions and summarizing results : analyzing and summarizing data in SQL server - Deardurff, John (Apress, 2019)
"The video begins with an introduction to basic functions to work with character data and NULL values. From there you'll move on to functions dealing with conditional structures, NULL values, and formatting. You'll also cover aggregate functions to average, count, and summarize data. Finally, this video discusses how to group result sets by a field using the GROUP BY clause, and how to filter those results after they have been grouped -- using the HAVING clause. Functions are the doorway to an ever-increasing number of powerful database engine features and capabilities. There is so much more that you can do in SQL other than simply SELECT data. Functions enable you to take full advantage of the power that's available to you in Microsoft's flagship database engine. This video is the second in a series and leaves you well positioned to step into the next video covering how to select data from multiple tables."--Resource description page